Plant therapy in the Peruvian Amazon (Loreto) in case of infectious diseases and its antimicrobial evaluation. (1st March 2020) - Roumy, Vincent; Ruiz Macedo, Juan Celidonio; Bonneau, Natacha; Samaillie, Jennifer; Azaroual, Nathalie; Encinas, Leonor Arévalo; Rivière, Céline; Hennebelle, Thierry; Sahpaz, Sevser; Antherieu, Sebastien; Pinçon, Claire; Neut, Christel; et al.
Abstract: Ethnopharmacological relevance: The plant species reported here are used in contemporary phytotherapies by native and neo-urban societies from the Iquitenian surroundings (district of Loreto, Peruvian Amazon) for ailments related to microbial infections. Inhabitants of various ethnic origins were interviewed and 81 selected extracts were evaluated for their antimicrobial properties against a panel of 36 sensitive and multi-resistant bacteria or yeast. Medicinal plant researches in the Peruvian Amazon are now significant, but none of them has focused on an exhaustive listing of identified species tested on so many microbes with standardized experiments (to obtain MIC value). Aim of the study: The aim of the study was to inventory the plants used against infections in the Loreto, an Amazonian region of Peru. It led to the new identification of secondary metabolites in two plant species. Materials and methods: Ethnographic survey was carried out using "participant-observation" methodology and focus on bioprospecting of antimicrobial remedies. Selected plant extracts and antimicrobial drugs were tested in vitro with agar dilution method on 35 bacteria strains and 1 yeast to evaluate their Minimal Inhibitory Concentration (MIC). Microdilution methods using 96-well microtiter plates were used for the determination of MIC from isolated compounds, and cytotoxicity in HepG2 cells from some selected extracts were also evaluated. Activity-guided isolation and identification of compounds were performed by various chromatographic methods and structural elucidations were established using HRMS and NMR spectroscopy. Results: This study outlined antimicrobial activities of 59 plant species from 33 families (72 single plant extracts and 2 fermented preparations), 7 mixtures, and one insect nest extract against 36 microorganisms. Of the 59 species analysed, 12 plants showed relevant antibacterial activity with MIC ≤0.15 mg/mL for one or several of the 36 micro-organisms ( Aspidosperma excelsum, Brosimum acutifolium, Copaifera paupera, Erythrina amazonica, Hura crepitans, Myrciaria dubia, Ocotea aciphylla, Persea americana, Spondias mombin, Swartzia polyphylla, Virola pavonis, Vismia macrophylla ). Examination by bioautography of E. amazonica, M. dubia and O. aciphylla extracts allowed the phytochemical characterization of antimicrobial fractions and compounds. Conclusion: This study suggested an a posteriori correlation of the plant extract antimicrobial activity with the chemosensory cues of the drugs and attested that those chemosensory cues may be correlated with the presence of antimicrobial compounds (alkaloids, tannins, saponosids, essential oil, oleoresin …). It also led to the first isolation and identification of three secondary metabolites from E. amazonica and M. dubia Graphical abstract: Image 1